Brand Image Communication Management for Nusak Termanu Kingdom to maintain Positive Images - Amalo, Vicoas Trisula Bhakti; Maella, Nurannafi Farni Syam; Prasetyo, Iwan Joko; Zulaikha, Zulaikha; Farida, Farida (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The seamless attainment of strategic objectives and the cultivation of a cohesive and engaged workforce This case study examines the strategies employed by the Nusak Termanu Kingdom to effectively communicate their brand image and maintain a positive public perception. Nusak Termanu, an indigenous monarchy in Indonesia, is compelled to safeguard its cultural heritage and distinctiveness in the face of modernization and globalization. The study employs concepts of brand image management, strategic communication, and organizational communication to understand how communication influences and maintains the public perception of a corporation. In order to establish a cohesive and captivating brand story, it is essential to align internal and external communication efforts, as emphasized in the literature. According to Robert K. Yin, the study employs a qualitative case study methodology. Data was collected by conducting comprehensive personal interviews with key stakeholders of the Nusak Termanu Kingdom, which included the royal family, communication managers, and community leaders. In order to triangulate the findings, one also examined relevant records and archival materials. The results reveal the many communication strategies employed by the Nusak Termanu Kingdom to manage its brand image. These encompass the intentional utilization of traditional and digital communication channels, the establishment of strategic partnerships, engagement with the local community, and alignment of internal and external communication endeavors. The report also highlights the primary possibilities and challenges that the monarchy encounters in managing its brand image. The research provides incisive analysis for cultural organizations and conventional enterprises grappling with the intricacies of brand image management in the digital era. It highlights the importance of employing a comprehensive and inclusive approach to communication that incorporates both traditional and contemporary methods in order to engage stakeholders and maintain a favorable public perception. The results establish a foundation for future research on brand image communication within traditional organizations and have practical significance for communication experts.